Antibiotics in Fetal and Early Life and Subsequent Childhood Asthma. Issue 4 (April 2015) - Örtqvist, Anne K.; Lundholm, Cecilia; Kieler, Helle; Ludvigsson, Jonas F.; Fall, Tove; Ye, Weimin; Almqvist, Catarina
<x xml:space="preserve">Abstract</x> ABSTRACT The increased use of antibiotics has occurred while there is also a rising incidence of childhood asthma. One concern is that the rise in asthma is due to either mothers receiving antibiotics during pregnancy or increased antibiotic use in infants and young children. No study to date has investigated the association between exposure to antibiotics from the start of pregnancy and childhood asthma while also accounting for the influence of familial confounders. This study was performed to examine the association between exposure to antibiotics in fetal life or childhood and development of asthma in children followed from start of their mother's pregnancy to school age. Data on parents and siblings, information on exposure, and outcomes were obtained from nationwide population-based registers. Antibiotics were categorized as "any antibiotics, " "airway antibiotics, " and "urinary tract or skin and soft tissue antibiotics" based on usual prescriptive use. Children were considered to have asthma if the diagnosis was made and they received 2 or more dispensed prescriptions for common asthma medications. Maternal asthma was defined as the mother having fulfilled the criteria of dispensed asthma drugs or a diagnosis of asthma made during the study period. The association between antibiotic exposure and asthma was analyzed in the entire cohort of children, with a sibling control design then used to adjust for familial factors and reported as hazard ratios (HRs). The controls were all full siblings who did not have asthma but were in the study when the index child developed asthma. Of 493, 785 children in the cohort analyses, 180, 894 were eligible for the sibling control analyses. Overall, 6% of the children in the cohorts had asthma, with 20% and 16% of those in the full and sibling cohorts, respectively, exposed to antibiotics in fetal life. At least 1 prescription of any antibiotic was filled for 62% of children in both cohorts; 4% of children in both cohorts were exposed to antibiotics in the hospital. Any antibiotic in fetal life was significantly associated with a 36% increased risk of asthma in childhood with a comparable increased risk for airway antibiotics (HR, 1.41; 95% confidence interval [CI], 1.37–1.46). The excess risk associated with urinary tract/skin antibiotics, although lower, was still associated with asthma (HR, 1.25; 95% CI, 1.20–1.30). After adjustment for confounding variables, antibiotic exposure in fetal life remained significantly associated with asthma but was reduced for any and airway antibiotics. In the sibling controls, the association disappeared; the adjusted HRs (aHRs) were 0.98 (95% CI, 0.90–1.07) for airway antibiotics and 0.98 (95% CI, 0.88–1.10) for urinary tract/skin antibiotics. In the overall cohort, the highest risk for asthma was among those children treated with antibiotics during childhood (aHR, 3.71; 95% CI, 3.41–4.03). When compared with sibling controls, all estimates were lower than in the overall cohort analyses (aHR, 2.11; 95% CI, 1.61–2.76). For both airway and urinary tract/skin antibiotics, cohort analyses showed a decreased HR with increasing age, but the difference in risk was more pronounced after exposure to airway antibiotics (aHR, 4.12, 95% CI 3.78–4.50) compared with urinary tract/skin antibiotics (aHR1.54; 95% CI, 1.24–1.92) in the youngest children. In analyses with sibling controls, estimates were decreased compared with the cohort analyses, where the association with airway antibiotics remained significant (aHR, 2.36; 95% CI, 1.78–3.13), and the association between urinary tract/skin antibiotics and asthma disappeared (aHR, 0.85; 95% CI, 0.47–1.55). Significant associations were found for all groups of antibiotics for exposure in first year of life and incidence of asthma from the age of 2 years in the cohort analyses, but in this subgroup, no associations remained statistically significant in the sibling control analyses. In the full cohort, a dose-response relationship was noted for an increasing number of prescriptions for all groups of antibiotics and asthma (P < 0.001, all age groups). In sibling analyses, the dose-response relationship remained for any and airway antibiotics (P < 0.001, all age groups), but not for urinary tract/skin antibiotics (P = 0.22–0.97 for different age groups). A positive association exists between exposure to antibiotics in fetal life/childhood and subsequent asthma. In siblings, these associations disappeared or decreased, suggesting that the association might be confounded by factors (eg, environment, inheritable) shared in families.